WASTE BANK MANAGEMENT DURING THE COVID-19 PANDEMIC AT BOGOR RAYA PERMAI HOUSING - Raharyanti, Fenny; Ariyo Bimo, Widhi; Azmia, Nora (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Household waste, not only removes it from the view of its inhabitants, but if it is managed better, it will bring benefits. Starting with general sorting based on organic and inorganic types, then it is necessary to practice separating inorganic waste by paying attention to its composition, whether paper, plastic, cans, styrofoam and other types. Waste bank is one solution in the management of inorganic waste. Community Service Activities from Faculty of Health Sciences and the Faculty of Economics and Business, Ibn Khaldun University, Bogor, provided support to the Baitussalaam Bogor Raya Permai Waste Bank, Curug Village, West Bogor City in November 2021 in the form of socializing the implementation of Waste Bank activities during the COVID pandemic. The method is picking up or visiting people who have difficulty accessing the segregated waste collection site. Due to human activities will continue to produce waste even during a pandemic, while health protocols must still be observed. In addition, the support of the students in data collection and weighing is very important in the success of this activity. The results of this activity become a learning platform for the importance of sorting household waste which can be converted into rupiah based on weight, so that the community can feel the economic and environmental health benefits.